Failure and dropouts An investigation into the relationship between students repeating a grade and dropout rates in Italy - Batini, Federico; Bartolucci, Marco; Bellucci, Chiara; Toti, Giulia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
In this paper we aim to investigate the relationship between school failures and early school leaving. The research objective was to verify, through the analysis of archive data of a sample of two high schools, whether the repetition of a school year somehow influenced early school leaving. Rather than encouraging students to engage more, repeating a school year has consequences like deterioration in school performance, problems in terms of social adaptation as well as a drop in motivation. What is more it could lead to a reduction in their self-esteem and perceived self-efficacy with respect to the educational path. Results show a statistically significant correlation between number of students who repeated a year and early school leaving, and no correlation between each of them and the number of students enrolled.